Decolonizing Islamic Education: Muslim Intellectual Critiques of Western Educational Hegemony during the Colonial Period - Hafizul Husni; Zuhdiyah; Maryamah; Nyayu Soraya (Program Pascasarjana Pendidikan Islam Universitas Islam Darul Ulum Lamongan, 2026)
This study examines the transformation of Islamic education during the colonial period and the intellectual responses of Muslim scholars to Western educational hegemony through a systematic literature review (SLR). Colonial expansion introduced modern secular schooling systems that significantly reshaped educational institutions in many Muslim societies. These reforms produced a dual educational structure in which Western schools operated alongside traditional Islamic institutions such as madrasah and pesantren, influencing knowledge hierarchies, language policies, and educational authority. Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol, this study systematically analyzed scholarly publications retrieved from the Scopus database to identify major themes and theoretical perspectives in the literature. The findings reveal four key patterns: the institutional transformation of Islamic education under colonial policies, the emergence of educational dualism, the intellectual responses of Muslim scholars to Western epistemological dominance, and the growing relevance of decolonial perspectives in contemporary educational debates. The review highlights the resilience of Islamic educational institutions in preserving religious knowledge traditions while engaging with modern knowledge. These findings contribute to discussions on the decolonization of education and the development of culturally grounded educational frameworks in Muslim societies.